Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.

Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation